2003
DOI: 10.1097/00002508-200307000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Does the Type of Arthroscopic Surgery Modify the Analgesic Effect of Intraarticular Morphine and Bupivacaine? A Preliminary Study

Abstract: The analgesic effect of morphine and bupivacaine is different depending on the type of arthroscopic surgery. Intraarticular bupivacaine is effective in surgeries with a low inflammatory response. For surgeries with a higher inflammatory response, morphine has a better analgesic effect. Postoperative intraarticular analgesic therapy should be indicated according to the performed arthroscopic procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 25 publications
1
44
0
2
Order By: Relevance
“…Marchal et al [19] assessed the different analgesic responses to intra-articular morphine, bupivacaine, and placebo in two different types of arthroscopic knee surgery under general anesthesia. Patients were grouped according to the degree of intra-articular damage into the low inflammatory surgery group (diagnostic arthroscopies, partial meniscectomy) and the high inflammatory surgery group (synovial plica removal, patellar shaving, lateral retinacular release, and anterior cruciate ligament reconstruction).…”
Section: Intra-articular Administrationmentioning
confidence: 99%
“…Marchal et al [19] assessed the different analgesic responses to intra-articular morphine, bupivacaine, and placebo in two different types of arthroscopic knee surgery under general anesthesia. Patients were grouped according to the degree of intra-articular damage into the low inflammatory surgery group (diagnostic arthroscopies, partial meniscectomy) and the high inflammatory surgery group (synovial plica removal, patellar shaving, lateral retinacular release, and anterior cruciate ligament reconstruction).…”
Section: Intra-articular Administrationmentioning
confidence: 99%
“…None of the patients included in the study requested to be excluded due to the side effects. In previous studies, the development of side effects was not a limiting factor for the use of IA morphine, both in arthroscopies and TKA 1,13,14,37,38 . When the side effects of this analgesic technique are compared to that of other techniques, similar percentage of episodes of nausea and vomiting are observed.…”
Section: Discussionmentioning
confidence: 88%
“…In the first group, bupivacaine was more effective with significant reduction in pain scores despite the lack of difference in analgesic consumption among the subgroups. Based on those results, the author 26 suggested that the lower expression of opioid receptors in the joint would be responsible for the reduced efficacy of morphine in the "little inflammatory" group 37 . In the present study, a different approach was used to evaluate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have reported that postoperative intra-articular morphine is effective only in patients with moderate or severe pain, 327,328 but others support the idea that inflammation is a prerequisite for the peripheral analgesic effectiveness of opioids. 329 Local anesthetics are considered effective short-term postoperative analgesics, whereas opioids produce more sustained intra-articular analgesia. A study by Marchal and colleagues 329 revealed that patients who had undergone "low inflammatory surgery" received greater short-term (4 to 8 hours) benefit from intra-articular bupivacaine, whereas those who had undergone "high inflammatory surgery" received greater long-term (24 hours) benefit from intra-articular morphine (5 mg).…”
Section: Intra-articular Morphinementioning
confidence: 99%
“…A study by Marchal and colleagues 329 revealed that patients who had undergone "low inflammatory surgery" received greater short-term (4 to 8 hours) benefit from intra-articular bupivacaine, whereas those who had undergone "high inflammatory surgery" received greater long-term (24 hours) benefit from intra-articular morphine (5 mg). 329 Intra-articular meperidine is favored by some practitioners because of its dual opioid and local anesthetic effect. In the literature, the dose of intra-articular meperidine varies from 50 to 200 mg. 330 Doses greater than 100 mg (which produce a higher circulating concentration of normeperidine) are associated with a higher incidence of side effects (nausea, vomiting, and somnolence).…”
Section: Intra-articular Morphinementioning
confidence: 99%